Integrating Religiosity into the Fraud Pentagon Model: An Empirical Analysis of Asset Misappropriation Risk in Governmental Organizations - Ratmono, Dwi; Cahyonowati, Nur; Lestari, Sari (International Review of Management and Marketing, 2025)
This study aims to integrate religiosity into the fraud pentagon or S.C.O.R.E model regarding asset misappropriation risk among government organization employees. Data were collected using a questionnaire survey involving 210 employees from a government organization in Indonesia who are tasked with managing assets. Data analysis was carried out using the partial least squares-structural equation modeling (PLS-SEM) method. This study found that stimulus, capability, opportunity, rationalization, and ego are positively related to asset misappropriation. In other words, the higher the five elements of fraud model, the higher the asset misappropriation risk. Conversely, religiosity is negatively related to asset misappropriation risk. The higher the religiosity of employees, the lower the tendency to commit asset misappropriation such as misusing office assets, creating fictitious documents, petty cash corruption, financial fraud, and others. This study recommends the development of an anti-fraud strategy for government organizations to mitigate the risk of asset misappropriation in the context of the fraud pentagon model. Furthermore, this study emphasizes the importance of religiosity as a factor that deters employees from committing asset misappropriation.